The role of sexually transmitted infections in the onset and development of chronic bacterial prostatitis - Diudiun, A.; Gubar, A. O.; Polion, М.; Polion, N.; Hladkykh, N.; Kryzhanovskyi, I.; Дюдюн, А.; Губарь, Андрій Олександрович; Поліон, М.; Поліон, Н.; Гладких, Н.; Крижановський, І. (My University, 2024)
Actuality. Emphasizing the role of sexually transmitted infections (STIs) in the development of chronic bacterial prostatitis. The purpose of the study is to analyze the role of STIs in the onset and development of an inflammatory process in the prostate gland. Materials and methods. The study included 375 patients with chronic prostatitis. The average age of patients is 24.8 ±2.4 years. Duration of the of the inflammatory process in the prostate gland for 1-3 years was 217 (32.0%), 4-6 years was 217 (57.9%), and 7–10 years was 38 (10.1%). Exacerbations of chronic disease occurred 1–2 times a year in 225 (60.0%) and 3–4 times a year in 71 (18.9%) patients. Physical, instrumental and specific laboratory tests are provided for by the regulations of the Ministry of Health of Ukraine. Results. A comparative analysis of the course and clinical and morphological manifestations of urogenital pathology in patients. STI was detected in 252 (67.2%) patients with chronic prostatitis. The anamnesis established in 294 (78.4%) patients with chronic prostatitis was the sanitation of STIs prescription of a dermatovenerologist, urologist or treatment on the recommendation of a sexual partner. Among the identified infectious agents, a mixed chlamydial-trichomonas infection prevailed. The combination of STIs with enterobacteriaceae was detected in 272 (72.5%) patients and in 74 (19.7%) with staphylococci. In 30 (8%) patients with chronic prostatitis had a monoinfectious agent. Conclusion. The most important sign of chronic prostatitis in men of the most sexually active age (18 to 42 years) is urethrogenic origin caused by chlamydial, trichomonas, ureaplasma and other urogenital infections, as well as their associations with opportunistic pathogens. Актуальність. Акцентування ролі інфекцій, які передаються статевим шляхом (ІПСШ) у розвитку виникнення хронічного бактеріального простатиту. Мета дослідження – проаналізувати роль інфекцій, які передаються статевим шляхом, у виникненні та розвитку запального процесу у передміхуровій залозі. Матеріал і методи. Під спостереженням перебувало 375 хворих на хронічний простатит. Середній вік пацієнтів – 24,8±2,4 року. Тривалість запального процесу в передміхуровій залозі 1–3 роки становила 217 (32,0%), 4–6 років – 217 (57,9%), 7–10 років – 38 (10,1%) пацієнтів. Загострення хронічного простатиту виникали 1–2 рази на рік у 225 (60,0%), 3–4 рази на рік – у 71 (18,9%) пацієнта. Фізикальні, інструментальні та специфічні лабораторні дослідження передбачено нормативними актами МОЗ України. Результати дослідження. Проведено порівняльний аналіз перебігу та клініко-морфологічних проявів урогенітальної патології у пацієнтів. ІПСШ виявлено у 252 (67,2%) хворих на хронічний простатит. Зібраний анамнез установив у 294 (78,4%) пацієнтів із хронічним простатитом факт санації інфекції, що передається статевим шляхом, за призначенням дерматовенеролога, уролога або лікування за рекомендацією статевого партнера. Серед виявлених збудників інфекції переважала змішана хламідійно-трихомонадна інфекція. Поєднання ІПСШ з мікроорганізмами типу ентеробактерій виявлено у 272 (72,5%) хворих та у 74 (19,7%) – стафілококами. У 30(8%) хворих на хронічний простатит виявлено моноінфекційний агент. Висновок. Найбільш важливою ознакою хронічного простатиту у чоловіків найбільш сексуально активного віку (від 18 до 42 років) є уретрогенне походження, спричинене хламідійною, трихомонадною, уреаплазмовою та іншими урогенітальними інфекціями, а також їх асоціаціями з умовно-патогенними мікроорганізмами.
Роль інфекцій, які переважно передаються статевим шляхом, у виникненні та розвитку хронічного бактеріального простатиту
Keywords: bacterial prostatitis; sexually-transmitted infections; transrectal ultrasound examination; chronic kidney disease; prostate-specific antigen; chlamydia; trichomoniasis; vasocongestion; бактеріальний простатит; інфекції, які передаються статевим шляхом; трансректальне ультразвукове дослідження; хронічна хвороба нирок; простатспецифічний антиген; хламідіоз; трихомоніаз; вазоконгестія